Contrast‐enhanced ultrasound assessed renal microvascular perfusion may predict postoperative renal complications following colorectal surgery. (1st May 2021) - Read, David J.; Doleman, Brett; Heinink, Tom; Selby, Nicholas M.; Lund, Jonathan N.; Phillips, Bethan E.; Williams, John P.
Abstract: Colorectal surgery is associated with an above‐average mortality rate of approximately 15%. During surgery, maintenance of vital organ perfusion is essential in order to reduce postoperative mortality and morbidity, with renal perfusion of particular importance. Oesophageal Doppler monitors (ODM) are commonly used to try and provide accurate measures of fluid depletion during surgery; however, it is unclear to what extent they reflect organ perfusion. In addition, it is not known whether macro‐ and/ or microvascular perfusion indices are associated with renal complications following colorectal surgery. Thirty‐two participants scheduled for colorectal surgery had three measures of macro‐ and microvascular renal blood flow via contrast enhanced ultrasound (CEUS), and simultaneous measures of cardiac output indices via ODM: (i) pre‐operatively; (ii) intra‐operatively at the mid‐point of operation, and (iii) after the conclusion of surgery. The Postoperative Morbidity Survey (POMS) was used to assess postoperative complications. Intra‐operatively, there was a significant correlation between renal microvascular flow (RT) and renal macrovascular flow (TTI) ( ρ = 0.52; p = 0.003). Intra‐operative TTI, but not RT, was associated with cardiac index ( ρ = −0.50; p =0.0003). Intra‐operative RT predicted increases in renal complications (OR 1.46; 95% CI 1.03–2.09) with good discrimination (C‐statistic, 0.85). Complications were not predicted by TTI or ODM‐derived indices. There was no relationship between RT and TTI before or after surgery. ODM measures of haemodynamic status do not correlate with renal microvascular blood flow, and as such are likely not suitable to determine vital organ perfusion. Only CEUS‐derived measures of microvascular perfusion were predictive of postoperative renal complications. Abstract : Adequate microvascular renal perfusion is essential to reduce postoperative morbidity and mortality after colorectal surgery. Oesophageal Doppler monitoring (ODM), the tool most commonly used to assess fluid requirements during surgery, does not represent microvascular renal perfusion, suggesting contrast enhanced ultrasound (CEUS) to be a better tool for this purpose.